KORELASI TENSIONTYPE HEADACHE DENGAN GANGGUAN KUALITAS HIDUP MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Evlyne Erlyana Suryawijaya,* I Putu Eka Widyadharma,* I Made Oka Adnyana* (Neurona Majalah Kedokteran Neuro Sains, 2017)
INTRODUCTION TENSIONTYPE HEADACHE TTH IS THE MOST COMMEN HEADACHE ESPECIALLY IN ADULT 3078 TTH AFFECTED QUALITY OF LIFE ESPECIALLY IN YOUNG ADULTS AS WELL AS UNIVERSITY STUDENT AMONG MEDICAL STUDENTS HIGH ACADEMIC LOAD IS WELL KNOWN TO CAUSE MENTAL AND PHYSICAL STRESS THAT LEADS TO A HIGH RISK OF TTH EVENT THUS IMPAIR QUALITY OF LIFE IF NOT IDENTIFIED AND WELL MANAGED